Legal Status of Adopted Children on Parents' Inheritance Based on Islamic Law and Civil Law (Case Study of Decision Number: 113/K/PDT/2019) - Teguh Imam Wahyudi; Gunawan Djajaputra (Jurnal Indonesia Sosial Teknologi, 2024)
The legal consequences of the adoption event are regarding the status of the adopted child as the heir of his adoptive parents, such a status often causes problems in the family. The issues that often arise in the event of a lawsuit are usually related to the legality of the adoption of the child, as well as the position of the adopted child as the heir of his adoptive parents. Adopted children also have the right to guarantee the protection of their rights so that they can live their lives, participate optimally, and get protection from violence and/or different treatments. As for the reality, sometimes adopted children are still considered not part of the family and in the end, the rights of adopted children are ignored. This does not rule out the possibility of problems such as in terms of the distribution of inheritance, because it considers that the adopted child is not the heir of the parent who adopted him. In this study, the author also used Decision Study Number: 113/K/Pdt/2019. The theories used in the research are the theory of legal certainty, the theory of legal justice and the theory of legal protection. The research method used by the author is a normative research method. SW is not entitled to LTJ's inheritance because of his position as only a foster child based on the Deed of Child Handover Number 2. Foster children in terms of inheritance are not entitled to inheritance because their position is different from the position of the adopted child. A foster child is considered a third person who is not included in the class of heirs who are entitled to inheritance according to the law. An adopted child can get property from his adoptive parents through a will. The amount of this will is determined not to exceed 1/3 of the inheritance.